Assessing the correlation between caffeine consumption and its effect on the academic performance of medical students of Shifa College of Medicine, Islamabad, Pakistan: A Cross-Sectional Study - Dawood Tahir, Dawood Tahir; Ibad Ur Rehman, Ibad Ur RehmanIbad Ur Rehman; Tatheer Zahra, Tatheer Zahra (Journal of Rawalpindi Medical College, 2022)
Background: To assess the correlation between caffeine consumption and its effect on the academic performance of medical students of Shifa College of Medicine, Islamabad, Pakistan. Methods: A descriptive cross-sectional study was conducted in Shifa College of Medicine and its affiliated hospital for about three months from 10th June, 2019 till 15th August 2019. Second-year medical students actively took part in it. We used convenient sampling; a total of 101 students eagerly participated in it. We used a detailed self-administered questionnaire in which simplified questions with four to five options were given. Participants marked their responses to the provided options. A correlation was noticed between their Locomotive System and Gastrointestinal System modular exam scores with the questionnaire response. Data were analyzed by SPSS version 23. Results: Out of 101 participants, 51.5% were males, and 48.5% were females. About 77.2% of participants were consuming caffeine in any form, while 22.8% never consumed caffeine. Those who consumed moderate (200-400 mg) caffeine in any way performed better in the Locomotive System Module with a mean score of 71.88%. Simultaneously, those who consumed a lot more than 400 mg of caffeine scored better in the Gastrointestinal Tract Module with a mean score of 76.50%. Conclusion: By conducting this study, we identified that caffeine consumption is surprisingly high in medical students. The correlation between caffeine consumption and its effect on medical students’ performance is not significant. Key Words: Academic performance, Caffeine consumption, Medical students. (Source: MeSH-NLM).